Assay of Commenila benghalensis Linn. Leaf Extract on Selected Microbes - Urvashi Sinha (Innovations in Microbiology and Biotechnology Vol. 7, 2022)
The present study was designed to investigate the antibacterial activity of leaf extract of C. benghalensis L. in order to examine the pharmacological basis of the use of the plant in folk medicine for the treatment of infectious diseases. The existence of tannin, favonoid, phenol, carbohydrate, and volatile oil was discovered in the chloroform extract, which demonstrated the greatest activity against the pathogenic bacterial strains Escherechia coli, Staphylococcus aureus, Salmonella typhi, and Candida albicans, with inhibition zones of 7mm, 1mm, 3mm, and 4mm, respectively, when compared to the hexane and methanolic extracts. The Minimum Inhibition Concentration (MIC) of the chloroform extract was determined using the dilution susceptibility test method. The current findings support the use of Commelina benghalensis L leaf extract as a therapeutic agent against common pathogenic microorganisms.